Omental patch reinforced with polypropylene mesh and split-thickness skin grafting: A new procedure to close the "open abdomen". (2016) - Muñoz Muñoz, Emilio; Pardo-Aranda, Fernando; García-Olivares, Esteban; Pontes De Sousa, Sandra Patricia; Forcada, Pilar; Veloso, Enrique
Highlights: The definitive closure of an open abdomen with a giant full abdominal defect remains a problem. The great omentum allows a rapid integration of the polypropylene mesh. The structure achieved does not hamper future surgical procedures. Abstract: Introduction: The "open abdomen" expression widely used to define a full-thickness defect of the abdominal wall intentionally made in some situations like abdominal compartment syndrome, has been replaced by a newest one called "laparostomy". The definitive closure of an open abdomen with a giant full abdominal thickness defect remains a problem. Case report: We present a 67-year old male with a descompressive laparostomy treated with a greater omentum flap sutured hermetically with interrupted stitches at the edges of the muscle wall, reinforced with large mesh of polypropylene (PP) placed on-lay and sutured to the fascia by two concentric running sutures of polypropylene. A vacuum-assisted closure device was placed on the second postoperative day and it was kept during three weeks. By then the PP mesh was completely integrated so skin grafts were applied to the surface of the granulation tissue. An incisional hernia was easily repaired at three years of follow-up. Eight months after the last surgery the patient is satisfied with the result achieved. Discussion: The great omentum has immunological and angiogenic properties that allow a rapid integration of the polypropylene mesh, even in septic environments, facilitating the engraftment of split-thickness skin graft. The reactive fibrosis caused by the PP mesh replaces the fat tissue but the inner surface is preserved, thereby avoiding subsequent adhesion and facilitates surgical access to the abdominal cavity if necessary in the future. Conclusion: The structure achieved is a strong structure, capable of visceral isolation that can be useful to close some OA.